2020
DOI: 10.1186/s12884-020-2792-7
|View full text |Cite
|
Sign up to set email alerts
|

Not just numbers: beyond counting caesarean deliveries to understanding their determinants in Ghana using a population based cross-sectional study

Abstract: Background: The increasing rate of caesarean deliveries (CD) has become a serious concern for public health experts globally. Despite this health concern, research on factors associated CD in many low-and -middle countries like Ghana is sparse. This study, therefore, assessed the prevalence and determinants of CD among child-bearing women aged 15-49 in Ghana. Methods: The study used data from the 2014 Ghana Demographic and Health Survey. The analysis was limited to mothers (n = 2742) aged 15-49 , who had given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 34 publications
7
22
0
Order By: Relevance
“…Other studies have demonstrated that mass media impacts women empowerment, including their ability to take household decisions on contraception [ 47 – 51 ]. For example, sexual partners who access diverse media platforms (e.g., television, radio, newspapers), communicate more about safer sexual practices and subsequently use contraceptives (e.g., condoms), and/or other family planning methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that mass media impacts women empowerment, including their ability to take household decisions on contraception [ 47 – 51 ]. For example, sexual partners who access diverse media platforms (e.g., television, radio, newspapers), communicate more about safer sexual practices and subsequently use contraceptives (e.g., condoms), and/or other family planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations might include the alterations in the coding of the study variables, which could potentially generate data extraction errors. However, no substantial modifications were done during coding and extraction within the current study [ 47 ]. Despite these limitations, the sample size allows for generalizability of findings in the studied countries because data used were nationally representative.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is also the possibility of social desirable inherent with self-reporting and recall bias from the respondents. Other limitations could be errors associated with data extraction and curation and coding of procedures in charts and tables [38]. However, the coding and data extraction did not go through substantial changes.…”
Section: Strengths and Limitationmentioning
confidence: 99%
“…In Ghana, Central, Northern and Upper East regions are considered among the regions where birth rate is very high [ 72 ]. The trend has been attributed to high rates of unintended pregnancies due to sociocultural norms within the regions that support polygamous marriages and large family sizes and inadequate access to contraceptives [ 51 , 73 , 74 ]. Hence, the higher likelihood of consistent condom use among never married men who live in those regions could be an intervention to reduce the high fertility rates in the region.…”
Section: Discussionmentioning
confidence: 99%